Study on the cracking of carbon anodes used in aluminium industry. (4th April 2021) - Amrani, Salah; Kocaefe, Duygu; Kocaefe, Yasar; Bhattacharyay, Dipankar; Bouazara, Mohamed; Côté, Jules
Abstract: Carbon anodes are used in aluminium electrolysis. Their quality plays a major role in the stability of cell operation and energy consumption. The improvement of the quality of carbon anodes is essential to respond to the many challenges the aluminium industry is facing with respect to issues related to carbon loss, energy use, cell performance, and production cost, especially for high amperage cells. The presence of cracks increases the anode resistivity, and, as a result, power consumption, production cost, and greenhouse gas emissions also increase. Therefore, it is important to know how the cracks form during anode production. An industrial measurement campaign was carried out at the Aluminerie Alouette Inc. (AAI) plant in Sept‐Îles, Québec, Canada. The effect of raw materials (type of coke, pitch, and butts), vibro‐compaction (vibro‐compactor type, balloon pressure, and vibration time), and the position of anodes in the baking furnace on anode cracking was investigated. It was found that the anode centre is the region that contains the most cracks compared to other parts of the anode. The cracks in the horizontal direction are more predominant than those in other directions. The raw materials and the operating parameters of each anode production step affect anode cracking. Abstract : Anode production process and the production steps where the anode cracks form.